Area of Wharton's jelly as an estimate of the thickness of the umbilical cord and its relationship with estimated fetal weight - Marussi Emilio F (Reproductive Health, 2011)
Abstract Background To build a reference curve for the area of Wharton's jelly (WJ) in low-risk pregnancies from 13 to 40 weeks and to assess its relationship with estimated fetal weight (EFW). Methods 2,189 low-risk pregnancies had the area of WJ estimated by ultrasound and the 10th, 50th and 90th percentiles calculated using a third-degree polynomial regression procedure. EFW by ultrasound was correlated with the measurement of the area of WJ. Results The area of WJ increased according to gestational age (R2 = 0.64), stabilizing from the 32nd week onwards. There was a significant linear correlation between area of WJ and EFW up to 26 weeks (R = 0.782) and after that 5t remained practically constant (R = 0.047). Conclusion The area of WJ increases according to gestational age, with a trend to stabilize at around 32 weeks of gestation. It is also linearly correlated with EFW only up to 26 weeks of gestation.